2002
DOI: 10.1194/jlr.m200035-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MTP expression in developing swine

Abstract: To define the developmental expression of microsomal triglyceride transfer protein (MTP) large subunit mRNA and protein, samples of small intestine and liver were collected from 40-day gestation fetal, 2-day-old newborn, 3-week-old suckling, and 2-month-old weanling swine. In fetal animals, MTP mRNA expression was high in intestine and liver. Postnatally, jejunal expression paralleled the intake of a high-fat breast milk diet and declined after weaning. Ileal expression was comparable with that of jejunum in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…2007). In addition, the amount and composition of dietary fatty acids play an important role in MTTP expression in developing swine (Lu et al. 2002) and this effect could also be maintained in growing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…2007). In addition, the amount and composition of dietary fatty acids play an important role in MTTP expression in developing swine (Lu et al. 2002) and this effect could also be maintained in growing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Mttp is expressed during embryonic and fetal development (Terasawa et al,1999; Shelton et al,2000; Levy et al,2001; Lu et al,2002). Mouse Mttp mRNA has been detected in the YS at embryonic day E9.5 (Terasawa et al,1999; Shelton et al,2000) and MTP large subunit has been immunodetected in the YS of 9‐day chicken embryos (Hermann et al,2000).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian MTP large subunit gene ( Mttp ) is expressed during development (Terasawa et al,1999; Shelton et al,2000; Levy et al,2001; Lu et al,2002) and seems to be essential, as all homozygous Mttp knockout mice have been reported to die during embryonic development (Raabe et al,1998). Genetic mutations of human Mttp causing the absence or length modifications of the protein are responsible for abetalipoproteinemia (Shoulders et al,1993; Sharp et al,1993).…”
Section: Introductionmentioning
confidence: 99%
“…MTP plays a key role in the transfer of lipids during lipoprotein assembly in liver and the intestine 1 . In swine, it has been shown that the MTP gene expression is regulated by dietary fatty acids 2 . Although deleterious mutations in MTP lead to abetalipoproteineamia, a recessive disorder characterized by the absence of plasma apolipoprotein B and the accumulation of triglycerides in the cytoplasm of liver and intestinal cells, it has been suggested that nucleotide variation in the MTP gene can predict hepatic secretion levels of lipoproteins in healthy men 3…”
mentioning
confidence: 99%
“…Nucleotide sequence: Pig genomic DNA was isolated from blood using a phenol–chloroform extraction. MTP porcine mRNA sequence 2 (GenBank accession no. ) was used to design primers in exon 17 (MTPe17‐FW) and exon 18 (MTPe18‐RV), assuming conservation with the previously described human MTP gene structure (GenBank , region: 24990685–25039330).…”
mentioning
confidence: 99%